A Role for RNA Viruses in the Pathogenesis of Burkitt's Lymphoma: The Need for Reappraisal - Corry van den Bosch (Advances in Hematology)
Certain infectious agents are associated with lymphomas, but the strength of the association varies geographically, suggesting that local environmental factors make important contributions to lymphomagenesis. Endemic Burkitt’s Lymphoma has well-defined environmental requirements making it particularly suitable for research into local environmental factors. The Epstein-Barr virus and holoendemic Malaria are recognized as important cofactors in endemic Burkitt’s Lymphoma and their contributions are discussed. Additionally, infection with Chikungunya Fever, a potentially oncogenic arbovirus, was associated with the onset of endemic Burkitt’s Lymphoma in one study and also with space-time case clusters of the lymphoma. Chikungunya Virus has several characteristics typical of oncogenic viruses. The Flavivirus, Hepatitis C, a Class 1 Human Carcinogen, closely related to the arboviruses, Yellow Fever, and Dengue, is also more distantly related to Chikungunya Virus. The mechanisms of oncogenesis believed to operate in Hepatitis C lymphomagenesis are discussed, as is their potential applicability to Chikungunya Virus.